sgRNA-shRNA Structure Mediated SNP Site Editing on Porcine IGF2 Gene by CRISPR/StCas9 - Sun, Yongsen; Yan, Nana; Mu, Lu; Sun, Bing; Deng, Jingrong; Fang, Yuanyuan; Shao, Simin; Yan, Qiang; Han, Furong; Zhang, Zhiying; Xu, Kun (Frontiers in Genetics, 2019)
A SNP within intron 3 of the porcine IGF2 gene (G3072A) has been previously reported to lead to increased lean deposition and decreased fat deposition in pigs. In this study, StCas9 derived from Streptococcus thermophilus together with Drosha-mediated sgRNA-shRNA structure were used to enhance the G to A base editing on the IGF2 SNP site, which we called ‘SNP editing’. Firstly, the nuclease activities of StCas9 as we previously reported and SpCas9 derived from Streptococcus pyogenes were compared by surrogate report assay, and our StCas9 demonstrated a comparable activity (19.68%) with the prevalently used SpCas9 (17.34%). Secondly, a sgRNA-shRNA structure, IGF2.sgRNA-LIG4.shRNA-IGF2.sgRNA, was constructed for both IGF2 gene targeting and LIG4 gene silencing, which displayed almost the same targeting efficiency with the single IGF2.sgRNA control in the surrogate report assay. Then, porcine PK15 cells were co-transfected with an ssODNs donor and the sgRNA-shRNA/StCas9 or the IGF2.sgRNA/ StCas9 expression vector. The SNP editing events were detected by the RFLP assay, Sanger sequencing as well as Deep-sequencing, and the sgRNA-shRNA/StCas9 group demonstrated much higher HDR-based editing efficiency. Finally, this study achieved effective gene editing on the SNP site in porcine cells using the novel sgRNA-shRNA/StCas9 system, which will facilitate the pig breeding research in the future.